Divergência genética entre Populações de melipona rufíventris (hymenoptera, apidae, Meliponinae) - Vasconcelos, Soraya Matos de (1998)
The stingless bee of the species Melipona rufiventrís, Lepelletier 1836, extending from northern Brazil extending to Santa Catarina, as well as other Meliponines have been greatly reduced by deforestation and burning of our forests, and by the indiscriminate action of the blackbirds. The huge territorial occupation of Melipona rufiventrís has caused the fragmentation of its populations and, concomitantly, its geographical isolation. Through molecular methods, the evolutionary relationships involved in the speciation process in their populations were estimated. Molecular analyzes allowed comparisons of nuclear DNA sequences and the mitochondrial 16S rRNA gene producing converted data that made it possible to estimate divergent sequences. populations analyzed. The analysis of 84 RAPD markers allowed the separation of three distinct groups with 27% genetic distance. Group 1 represented by the population of Minas Gerais as the most genetically distant from the others. Group 2 represented by the population of Santa Catarina as the second most divergent and the third group represented by the populations of Espírito Santo, Bahia, Piauí and Maranhão. There was great intra-population similarity for all sampled populations. Slight similarity was found among populations except the closest geographically, such as Piauí and Maranhão, and between Espírito Santo and Bahia. Analysis of mutations of the 16S rRNA mitochondrial gene fragment by the SSCP technique revealed three haplotypes among the populations analyzed. The first brought together the populations of Maranhão, Piauí and Bahia. The second group was formed by the populations of Santa Catarina and Espírito Santo and the third by the population of Minas Gerais. There was agreement between the nuclear and mitochondrial DNA divergence rates (for the analyzed gene). There was variation among the results obtained by the methodologies employed for the population of Espírito Santo. The same haplotype was obtained for the populations of Santa Catarina and Espírito Santo, and such populations by RAPD markers are in different groups. These results reveal a possible contact zone between two groups with different evolution rates for nuclear and mitochondrial DNA.